2014
DOI: 10.3892/ol.2014.2363
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric comparison of intensity modulated and volumetric arc radiation therapy for gastric cancer

Abstract: The aim of the present study was to compare radiotherapy treatment plans for gastric cancer using intensity-modulated radiotherapy (IMRT) and single/double-arc volumetric modulated arc therapy (SA/DA-VMAT) delivery techniques. A total of 29 postoperative gastric cancer patients were enrolled in this study and each patient was scheduled 5-field IMRT (5F-IMRT), 7-field IMRT (7F-IMRT), SA-VMAT and DA-VMAT techniques. Dose-volume histogram statistics, conformal index (CI), homogeneity index (HI) and monitor units … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
4
9
0
Order By: Relevance
“…In this study, there was 53% reduction in average number of MUs and 76% reduction in measured treatment time with VMAT plans compared with swIMRT plans ( P < 0.001). This is consistent with other published studies that have compared VMAT and IMRT . The shorter treatment time may translate in improved workflow within a radiation department, as typical IMRT slots are 25–30 min long .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, there was 53% reduction in average number of MUs and 76% reduction in measured treatment time with VMAT plans compared with swIMRT plans ( P < 0.001). This is consistent with other published studies that have compared VMAT and IMRT . The shorter treatment time may translate in improved workflow within a radiation department, as typical IMRT slots are 25–30 min long .…”
Section: Discussionsupporting
confidence: 90%
“…Similar to published literature, D95 in this study was comparable between VMAT and IMRT plans ( P > 0.5); however, CI was statistically improved in favor of VMAT ( P < 0.001). The target volumes in this study, however, were significantly larger than reported by others.…”
Section: Discussionsupporting
confidence: 80%
“…In combination with the Monaco treatment planning system (TPS), Erasmus-iCycle is currently used in clinical practice for IMRT and VMAT plan generation for prostate, head and neck, cervical and lung cancer patients [ 19 22 ]. Several studies on postoperative gastric cancer patients have dosimetrically evaluated different radiotherapy techniques [ 23 26 ]. To our knowledge, no study has been published considering the feasibility and advantages of automated treatment planning for this treatment site.…”
Section: Introductionmentioning
confidence: 99%
“…SAVMAT showed improved left kidney and liver dose sparing compared with 3DCRT, whereas it failed to show an advantage over the IMRT technique. Li et al 47 compared IMRT plans with single-/double-arc VMAT plans and found that double-arc VMAT showed improved tumour coverage and better kidney dose sparing than five-field (5F)-IMRT, and 5F-IMRT and SAVMAT, whereas no advantage was observed regarding liver dose sparing. Hu et al 48 adopted beam angle and multicriteria optimization for IMRT and compared it with the VMAT technique, which showed similar target coverage and OAR sparing.…”
Section: Volumetric Modulated Arc Therapymentioning
confidence: 99%
“…Lesser monitor units and continuous delivery enable VMAT to treat patient with gastric cancer within a shorter time than when using the IMRT technique. 47,48 Proton beam radiation therapy Limited data are available to assess the outcomes of proton beam radiation therapy. A few case reports showed the efficacy of this technique; one study revealed persistent gastric ulcers at the primary lesion without remaining cancer cells after radiation, and another study showed ,5% of residual tumour tissue.…”
Section: Volumetric Modulated Arc Therapymentioning
confidence: 99%